2018
DOI: 10.1503/jpn.170116
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive, emotional and neuroendocrine correlates of exposure to sexual assault in women

Abstract: Dysfunctions in the dorsal anterior cingulate cortex and the cerebellum may represent early functional brain modifications that alter higher cognitive processes when emotional material is involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In addition to lower morning cortisol in victims three weeks following exposure to sexual assault , this study indicates that victims who developed PTSD at the six‐month follow‐up, showed higher midday cortisol concentrations relative to the victims who did not develop PTSD. These findings are at odds with previous meta‐analytical results indicating lower afternoon concentrations relative to morning cortisol measures in chronic PTSD female victims of sexual assault .…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…In addition to lower morning cortisol in victims three weeks following exposure to sexual assault , this study indicates that victims who developed PTSD at the six‐month follow‐up, showed higher midday cortisol concentrations relative to the victims who did not develop PTSD. These findings are at odds with previous meta‐analytical results indicating lower afternoon concentrations relative to morning cortisol measures in chronic PTSD female victims of sexual assault .…”
Section: Discussionmentioning
confidence: 70%
“…For the first time, this study investigated the longitudinal neuroendocrine (diurnal cortisol) and neuroanatomical (hippocampal and amygdala volumes) changes occurring in females three weeks (T1) following exposure to sexual assault, and the associations of these changes with the development of PTSD at a six months (T2) follow‐up assessment. In addition to lower morning (8:00am) cortisol , females exposed to sexual assault at T1 had smaller hippocampal volumes, but not amygdala, and similar total diurnal cortisol changes (AUCg) relative to females who have never been exposed to sexual assault. At T2, victims who developed PTSD (PTSD+) had higher cortisol concentrations at 24:00 h relative to those who did not (PTSD−), but groups (PTSD+, PTSD− and controls) showed similar total diurnal cortisol changes (AUCg), and hippocampal and amygdala volumes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations